A reescrita colaborativa de textos: uma alternativa qualitativa para ressignificar a produção textual no Ensino Fundamental - Barros, Aterciana Fonseca de Vasconcelos (2015)
In recent decades, in many countries, including Brazil, it has intensified the discussions about improving the quality of education in the country. These discussions focus mainly on the implementation of teaching practices that contribute to form readers and proficient text producers, able to interact through the in writing different communicative contexts. Keeping this in view, this dissertation chooses as study object, the text production process writing, with an emphasis on rewriting process in school context of elementary school. Therefore, we elaborated a pedagogical intervention project developed from a didactic sequence, organized around "fables" gender and built from the teaching modules suggested by SCHNEUWLY and DOLZ (2004). In this direction, we aimed to investigate how a mediating performance of the teacher, in the process of students textual rewriting, contributes to the student improve significantly his text. We also aim to observe how the verbal interaction among pairs from the shared discussion of written guidelines from the teacher promotes revisions and changes that result in qualitative improvement of the written text. Theoretically, we seek contributions in literacy studies, (KLEIMAN, 1995); in writing approaches (OLIVEIRA, 2001); in collaborative writing process and Bakhtin's conception of language (Bakhtin, 2003[1953]). Methodologically, this critical ethnographic study is part of Applied Linguistics and adopts a qualitative approach of interpretive and collaborative research. Data analysis allows observing the importance of rewriting collaborative process in the appropriation skills to produce a written text and the consolidation of the practice of reviewing texts as an inexhaustible source of reflection, learning and continuous improvement, thus contributing to the formation of critical readers and proficient text producers.